Education as a positional good for marked-based reforms of state schooling: paper presented at the ECER 2000-conference in Edinburgh 20 - 23 September 2000 - Nick Adnett; Peter Davies (Forschungsinstitut für Bildungs- und Sozialökonomie (FiBS), 2000)
Analyses of market-based reforms of state schooling have occasionally acknowledged positional elements in parental demand, but none has fully examined their nature and implications. Contrary to the normal predictions of orthodox economic analysis, competition in positional markets can result in inefficient outcomes. Predominantly relying upon recent British experience, we examine the extent to which compulsory schooling can be viewed as a positional good and explore its implica-tions for policy. In particular, we consider whether policies targeting increases in parental choice assist a rise in the overall level of educational attainment.
Keywords: I20; I28; D11; 330; schooling choice; educational markets; positional good; status competition